Estimação do efeito das motocicletas na capacidade de interseções semaforizadas - Torquato, Roberto Matheus Nunes (2019)
One of the main activities of traffic engineering is the estimation of the capacity of approximations of signalized intersections. Most of the traffic engineering studies do not consider the participation of motorcycles in vehicular flows, since it is considered that they do not significantly impact the fluidity of usual traffic. However, studies carried out in Asian countries – which have a high number of motorcycles in the vehicle fleet – indicate that motorcycles have significant effects on start-up lost time and on saturation headways. In Brazil, since the 1990s, there has been a significant increase in the acquisition of motorcycles, mainly due to dissatisfaction related to the level of service offered by public transportation and the credit facility. Currently, the percentage of motorcycles in the vehicle fleet is 26% in Brazil and 49% in Ceará, reinforcing the relevance of the main aim of this work: to evaluate the effect of motorcycles on the capacity of a signalized intersection in Fortaleza. To accomplish this goal, variables that represent the presence of motorcycles in front of the first vehicle in the row were collected: distance between vehicles longitudinally and between vehicles laterally (virtual corridor). From collected data, descriptive correlational analysis and linear regression models were developed in order to determine and evaluate the effect of motorcycles on the start-up lost time, on the discharge headway and on the saturation flow. In addition, the passenger-car equivalence factor of motorcycles were also analyzed. The results showed that the average effect of a motorcycle positioned ahead or between vehicles in the initial lost time is between 0.3 and 0.7 seconds. However, there was no evidence that motorcycles positioned in the virtual corridor (space formed by the gap between vehicles from two adjacent traffic lanes) influence the discharge headway. As for the discharge headways in saturation regime, the results indicated that a motorcycle in front of the vehicle increases the headway by approximately 0.7 seconds, which represents a 30% increase in the light vehicle's headway. According to the models developed, the 1% increase in the proportion of motorcycles positioned longitudinally between vehicles during the saturation regime decreases the saturation flow between 4 and 6 vehicles per hour. The vehicle equivalence factor for motorcycles varies between 0.15 and 0.21, considering only those that were positioned longitudinally between vehicles.